2014
DOI: 10.1186/1472-6963-14-256
|View full text |Cite
|
Sign up to set email alerts
|

Peer support for stroke survivors: a case study

Abstract: BackgroundInnovative and sustainable programs are required to support the well-being of stroke survivors. Peer support is a potentially low cost way to enhance well-being of recent stroke survivors and the well-being and community reintegration of their peer supporters. This article describes the perceptions of stroke survivors, care partners, peer supporters, and professionals of an individual peer support program.MethodsAn instrumental case study design was used to examine a volunteer peer support program th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
64
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(69 citation statements)
references
References 19 publications
5
64
0
Order By: Relevance
“…Recent research into using peer support to support and reintegrate stroke survivors back into the community (Kessler et al . ) may also be an ideal intervention for church‐based outreach work.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent research into using peer support to support and reintegrate stroke survivors back into the community (Kessler et al . ) may also be an ideal intervention for church‐based outreach work.…”
Section: Discussionmentioning
confidence: 99%
“…At the very minimum, programmes that aim to increase medication compliance and adherence or that provide social or emotional support may be beneficial in post-stroke care. Recent research into using peer support to support and reintegrate stroke survivors back into the community (Kessler et al 2014) may also be an ideal intervention for church-based outreach work.…”
Section: Discussionmentioning
confidence: 99%
“…Ruth Wobma, MSc 1 , Rinske H. M. Nijland 1 , PhD, Johannes C. F. Ket 2 and Gert Kwakkel, PhD 1,3,4 From the 1 Amsterdam Rehabilitation Research Center, Reade, 2 Medical Library, VU University, 3 Department of Rehabilitation Medicine, MOVE Research Institute, VU University Medical Center, and 4 Department of Rehabilitation Medicine, Neuroscience Campus Amsterdam, VU University Medical Center, Amsterdam, The Netherlands programmes are designed to support this adjustment as they focus on interventions to: (i) restore impairments, (ii) regain the ability to perform activities of daily living, and (iii) find a new balance in areas such as relationships, work and daily and social life. Healthcare professionals are regularly brought together in a multidisciplinary team in order to meet the diversity of the health issues.…”
Section: Evidence For Peer Support In Rehabilitation For Individuals mentioning
confidence: 99%
“…Everyday functioning, societal participation and quality of life can be greatly affected by acquired brain injury (ABI). For most patients changes are permanent and their expectations and future plans have to be adjusted drastically (1,2). Rehabilitation…”
Section: Introductionmentioning
confidence: 99%
“…Although not an original aim, the study has, in line with past research, highlighted the value of peer support -in particular, participation in a stroke club -to persons with experience of stroke (see Beesley et al 2011;Carlsson, Möller, and Blomstrand 2009;damush et al 2007;Ch'ng, French, and Mclean 2008;Kessler, egan, and Kubina 2014;Lennon et al 2013;Lock et al 2005;Mayo et al 2015). Addressing an overlooked area, with stroke clubs being an understudied variety of peer support (Morris and Morris 2012), the study found that these groups were valued for providing individuals with opportunities to meet others in similar circumstances, visit interesting places and take part in enjoyable activities.…”
Section: Resultsmentioning
confidence: 59%